Difusión de las revistas españolas de ciencias sociales y humanidades. Acercamiento bibliométrico - Osca Lluch, Julia; Mateo Marquina, M.ª Elena (Revista General de Información y Documentación, 2003)
The purpose of this work is to give an account of current Spanish journals covering the fields of Social Sciences and the Humanities and to give information about current Spanish journals which are indexed by the various national and international databases. Also featured is the circulation of these several journals in major national and international databases, details about the editing institution, scientific discipline periodicity, language and document type.